THE ROLE OF THE SCIENTIFIC LIBRARIES IN ENSURING PRINCIPLES OF ACADEMIC INTEGRITY - Nina Batechko; Alla Durdas; Tetyana Kishchak; Mykola Mykhailichenko (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article deals with the role of the scientific libraries in ensuring principles of academic integrity as a component of higher education quality. The basic principles of academic integrity (honesty, trust, fairness, respect, responsibility) have been analyzed. The importance of these principles in the academic environment has been substantiated. The participation of the scientific libraries in raising awareness of plagiarism, correct citing using APA and MLA has been covered. Librarians' possibility to do much more in ensuring academic integrity has been found out. The role of the scientific libraries as data quality hubs has been highlighted and their functions as centers where much of the institution's research and publishing come together. The role of a librarian in promotion of academic integrity practices has been stated in the article. The importance of understanding internal and external factors that cause academic dishonesty has been stressed. The experience of Ukrainian scientific libraries in ensuring the principles of academic integrity has been studied. The role of the Ukrainian Library Association in realization of principles of academic integrity has been stated. starting in 2016, the Ukrainian Library Association has created the project «The Culture of Academic Virtue, the Role of Libraries» which is supported by the US Embassy in Ukraine. Representatives of various scientific libraries that are directly interested and involved in observing academic integrity in their institutions can take part in this project. The acquisition of competencies in the observance of academic integrity has been recognized as a long process of training and improvement. The beginning of the Movement for Academic Integrity in Ukraine has been highlighted. The role and experience of libraries in ensuring the principles of academic integrity with be the subject of further research.